2021
DOI: 10.3390/biology10060507
|View full text |Cite
|
Sign up to set email alerts
|

New Insights on Leptospira Infections in a Canine Population from North Sardinia, Italy: A Sero-Epidemiological Study

Abstract: Leptospirosis is a widespread zoonosis recognized as a re-emerging infectious disease in a wide variety of animal species, including humans and dogs. No data exist regarding the presence of Leptospira species in the canine population of Sardinia Island. This study reports the first sero-survey for leptospirosis in kennel and owned dogs from six areas of the north of Sardinia. Sera from 1296 dogs were tested by microscopic agglutination test (MAT) specific for nine different serovars that are known to be well w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 52 publications
(78 reference statements)
2
15
1
Order By: Relevance
“…Serological detection of pathogenic Leptospira strains from asymptomatic dogs was recently reported in Sardinia [18]. In the same study, Leptospira seropositivity was not correlated with shedding of the bacteria in dog urine and both rt-PCR and urine culture gave negative results.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…Serological detection of pathogenic Leptospira strains from asymptomatic dogs was recently reported in Sardinia [18]. In the same study, Leptospira seropositivity was not correlated with shedding of the bacteria in dog urine and both rt-PCR and urine culture gave negative results.…”
Section: Discussionmentioning
confidence: 66%
“…All serum samples were subjected to the microscopic agglutination test (MAT), test as previously described [18]. MAT was performed using a panel of 9 serovars comprising of leptospires from the Mediterranean area.…”
Section: Microscopic Agglutination Test (Mat)mentioning
confidence: 99%
See 2 more Smart Citations
“…Until now, vaccination against Leptospira is recommended in order to prevent the severe clinical diseases in dogs, more commonly caused by serovar Icterohaemorrhagiae in the northeast of Italy [12]. Furthermore, the most recent studies reported that vaccination of dogs with the new anti-Leptospira vaccine induces protective immunity against systemic disease, renal infection, and clinical signs [20], even if the available commercial vaccine formulations are not able to protect the dogs from Leptospira infection caused by emergent serogroups (Pomona, Sejroe) [21][22][23][24]. The widespread emergence of Leptospira strains requires the employment of specific diagnostic methods (MAT, molecular analysis, and genotyping) in order to better understand geographical distribution and to develop appropriate vaccine formulations.…”
Section: Discussionmentioning
confidence: 99%